The DNA Barcode of cytb on Selais Bungkuk Fish (Hemisilurus heterorhynchus Bleeker) Originating from Riau, Indonesia - Roza Elvyra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Selais bungkuk (Hemisilurus heterorhynchus Bleeker) is one of catfishes which is a member of family Siluridae and order Siluriformes. Selais bungkuk is an endemic fish in Riau Province. The scientific study of this fish is still limited including DNA barcoding study. This research aims to analyze the DNA barcode of cytochrome b (cytb) on selais bungkuk. Methods included colleting the fishes from Kampar River (three individuals) and Tapung River (three individuals); total DNA extraction from the muscle; electrophoresis, PCR, sequencing; and bioinformatics analysis. In this study, cytb DNA sequences were obtained from the six individual fishes studied with a size of 339 bp. The six sequences have been registered at GenBank with registration numbers MH633750, MH633751, MH633752 from Kampar River, MH633753, MH633754, and MH633755 from Tapung River. The BLASTn analysis showed that the selais bungkuk fish had the highest similarity of 92.63% with H. mekongensis and the lowest (90.00%) with selais janggut (Kryptopterus limpok). There were three nucleotides that characterize the selais bungkuk fish based on the cytb sequence such as nucleotide number 205, 229, and 280. The cytb sequence can distinguish groups of catfish separately based on their species. Conclusions and recommendations, the cytb sequences obtained in this study are the first to be reported in selais bungkuk fish and can be used as a reference for identifying this species.